2023
DOI: 10.7821/naer.2023.1.1240
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Impact of Artificial Intelligence and Computational Sciences on Student Performance: Systematic Review and Meta-analysis

Abstract: Artificial intelligence (AI) and computational sciences have aroused a growing interest in education. Despite its relatively recent history, AI is increasingly being introduced into the classroom through different modalities, with the aim of improving student achievement. Thus, the purpose of the research is to analyse, quantitatively and qualitatively, the impact of AI components and computational sciences on student performance. For this purpose, a systematic review and meta-analysis have been carried out in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 77 publications
1
11
0
5
Order By: Relevance
“…= 0.823. [68,69,70] were parallel with the findings of the current study in contributing to understanding the relationship between time spent studying at home and technology-aided instruction. While not all studies explicitly quantify the time aspect, they collectively underscore the importance of engagement quality, effective online learning strategies, and the positive impact of technology on academic achievement.…”
Section: Reject H01 Significantsupporting
confidence: 71%
“…= 0.823. [68,69,70] were parallel with the findings of the current study in contributing to understanding the relationship between time spent studying at home and technology-aided instruction. While not all studies explicitly quantify the time aspect, they collectively underscore the importance of engagement quality, effective online learning strategies, and the positive impact of technology on academic achievement.…”
Section: Reject H01 Significantsupporting
confidence: 71%
“…Among the related studies, Kung et al [ 3 ] provided insights that since medical students, along with their classmates, have proven the use of ChatGPT as an assistive tool expressing a significance on perceived relatedness. The findings of the current study demonstrated that if students would utilize CAI in general as an academic tool, it would be easy for others to adopt this as well [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…En la misma línea, afirmado por (García-Martínez et al, 2023y Litardo et al, 2023 en la IA aplicada a la educación superior, se utilizan diversos enfoques y metodologías para mejorar los procesos de enseñanza y aprendizaje. Entre los enfoques más comunes se encuentran el: a) aprendizaje automático, que permite personalizar la educación según las necesidades individuales de los estudiantes; y, b) el procesamiento del lenguaje natural, que facilita la interacción entre humanos y computadoras.…”
Section: Estado Del Arteunclassified
“…Este enfoque basado en datos está siendo utilizado para identificar patrones de aprendizaje, proporcionando retroalimentación personalizada y ayudando a los educadores a tomar decisiones fundamentadas. Sin embargo, también se han planteado preocupaciones sobre la privacidad de los datos, la equidad en el acceso a estas tecnologías y la dependencia en la automatización de procesos educativos (García-Martínez et al, 2023).…”
Section: Introductionunclassified